Novel lattice upgrade studies for diamond light source - Bartolini, R; Bailey, C; Cox, M; Hammond, N; Kay, J; Longhi, E; Mhaskar, S; Pulampong, T; Walker, R (2013)
Many synchrotron radiation facilities are studying lattice upgrades in order to lower the natural emittance and hence increase the radiation brightness. At Diamond we are pursuing a novel alternative, not targeting the minimum possible emittance but instead introducing additional insertion device (ID) straights and hence increasing the capacity of the facility, while still possibly achieving a more limited reduction in emittance. The new scheme involves converting some of the DBA lattice cells into a double-DBA or DDBA, with a new ID straight between the two achromats. We present here the design concept and preliminary lattice design, and discuss the challenging magnet and engineering issues. Copyright © 2013 by JACoW.